Improving Learning Outcomes Through Interactive Learning Media Based on Macromedia Flash - Suprapto, Yuyun; Pambudiyatno, Nyaris; Maharani Sukma, Meita; Bagus Harianto, Bambang; Irfansyah, Ade (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In order to adapt to the curriculum changes from 2016 to 2020 in the Air Navigation Engineering D3 Program, an innovative approach utilizing interactive learning media is required. This aims to support curriculum transformation due to technological advancements and the needs of the professional world. Therefore, the objective of this research is to assess the improvement of learning outcomes through the use of interactive learning media in teaching about navigation aids. The research subjects are D3 Air Navigation Engineering 13th Alpha and Bravo cohorts. Data collection was obtained from learning outcomes through Evaluation and Interactive Learning Media on Flight Navigation Aids. This research is a quasi-experimental quantitative study using pretest-posttest design. The conclusion drawn from the review and data analysis, to assess the validity using SPSS, is that the calculated r-value (r) is greater than the critical r-value (r 0.30), indicating that the questionnaire items are valid. Meanwhile, for the reliability test results, a Guttman SplitHalf coefficient correlation value of 0.929 was obtained, which is ≥ 0.80. The Cronbach’s Alpha value was 0.861. It can be concluded that all items of the ability variable (x) are valid. The pre-test and post-test scores in the control group were 40 and 75, respectively. Whereas in the experimental group, the class provided with interactive learning media obtained pre-test and post-test scores of 45 and 85, respectively. Therefore, this learning media can lead to increased student engagement and a significant improvement in their academic success